Narasi Politik Pasangan Calon Bupati dan Wakil bupati Perempuan Annisa Suci Ramadhani Dan Leli Arni Dalam Pilkada 2024 Di Kabupaten Dharmasraya - Yesi Sumarni; Emeraldy Chatra; Rahmi Surya Dewi (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2025)
This study aims to analyze the political narratives, social activities, and public support narratives constructed by the female regent candidate pair, Annisa Suci Ramadhani and Leli Arni, during the 2024 Regional Election (Pilkada) in Dharmasraya Regency. Their election as the first female regent and vice-regent in Dharmasraya marked a significant milestone in local politics, amidst challenges such as gender-based rejection, family-related issues, and the political condition of running unopposed against a “blank box.” This research employs a qualitative approach with a case study method and a constructivist paradigm. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model as well as Gérard Genette’s narratology theory. The findings reveal that the political narratives constructed by the candidate pair focused not only on priority programs such as education, agriculture, MSMEs, and youth empowerment but also on educating the public about women's leadership roles in custom, religion, and governance. These narratives were conveyed using simple, inclusive, and non-confrontational language, including rational and emotional arguments to counter the “blank box” option. Various social activities—such as group exercises with women, religious gatherings, public discussions, market visits, customary meetings, and youth dialogues became effective communication channels that fostered trust, dismantled gender bias, and built emotional closeness with the community. Public support narratives emerged from traditional leaders, youth figures, women leaders, and general citizens, including those who initially opposed the candidacy but later offered strong support after witnessing the candidates’ consistency and empathy. This study concludes that structured political narratives, when combined with socially relevant and emotionally resonant activities, can serve as an effective communication strategy to garner electoral support particularly in promoting female leadership in culturally traditional regions.